2014
DOI: 10.1007/s11010-014-2290-1
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate inhibits differentiation of C3H10T1/2 cells into adipocyte

Abstract: Mesenchymal stem cells (MSCs) can differentiate into a number of cell types, including adipocytes and osteoblasts. MSC differentiation into adipocytes inhibits osteogenic differentiation and vice versa. Therefore, understanding the mechanisms of MSC differentiation at the signaling level can lead to the development of novel therapeutic strategies toward tissue regeneration. Sphingosine-1-phosphate (S1P) is a signaling molecule that regulates many cellular responses, including cellular differentiation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
(66 reference statements)
3
39
1
Order By: Relevance
“…It is generally believed that the induction of osteoblastogenesis of MSC leads to the inhibition of adipogenesis and vice versa (Cawthorn et al, ; Rahman et al, ). The current study and our recent study (Hashimoto et al, ) indicate that S1P may regulate both the promotion of osteoblastogenesis and the suppression of adipogenesis in MSC. Therefore, we speculate that S1P may be a suitable therapeutic agent for senile osteoporosis, which is characterized by both an increased number of adipocytes and a decreased number of osteoblasts.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It is generally believed that the induction of osteoblastogenesis of MSC leads to the inhibition of adipogenesis and vice versa (Cawthorn et al, ; Rahman et al, ). The current study and our recent study (Hashimoto et al, ) indicate that S1P may regulate both the promotion of osteoblastogenesis and the suppression of adipogenesis in MSC. Therefore, we speculate that S1P may be a suitable therapeutic agent for senile osteoporosis, which is characterized by both an increased number of adipocytes and a decreased number of osteoblasts.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, our experimental system may not be suitable for the observation of OC expression. However, our previous studies showed that S1P enhanced osteoblastmediated calcification in osteoblast-like MC3T3-E1 cells (Matsuzaki et al, 2013) and in C3H10T1/2 cells (Hashimoto et al, 2015). Consequently, understanding the role of S1P in MSC differentiation is important for facilitating bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, S1P/S1PR1 also regulates osteoclastogenesis [17]. However, we have previously demonstrated that a substantial amount of S1PR2 mRNA is expressed in osteoblast-like cells [10], C3H10T1/2 cells (mesenchymal stem cell-cell lines) [18]. Gi-independent S1P/S1PR2 signaling also activates RhoA/Rho kinase (ROCK) in smooth muscle cells and CHO cells [19,20].…”
Section: Introductionmentioning
confidence: 79%
“…Recent studies have suggested that S1P may play an important role in the regulation of osteogenesis. Specifically, these studies have shown that S1P promotes osteogenic differentiation of precursor cells and inhibits their adipogenic differentiation [4749]. Future studies have to determine the exact mechanisms of how ANK affects osteogenic and adipogenic differentiation of precursor cells.…”
Section: Discussionmentioning
confidence: 99%